Niebezpieczeństwo. Odpowiedzialność. Przebudzenie. Wspomnienia z getta w Krakowie i z KL Płaszów - Kaszyński, Hubert; Maciejewska, Olga (Studia Edukacyjne, 2020)
The aim of the article is to present the issue of educational work carried out in a spirit of axiological education in the former Krakow ghetto and the former labor and concentration camp Plaszow in Kraków. The significance of the activities consists of the acquisition of knowledge about the difficult local history of the Holocaust and its heritage by confrontation with the ghetto and the former camp and relics of the past. The key area for dealing with the issues of harm, responsibility and awakening is social work, which in its axiological aspect largely focuses on reflection on the theory and practice relating to the complex issue of responsibility. These activities not only stimulate the historical awareness of totalitarianisms and the memory of them in the social and moral dimension, but also and most importantly they are a precondition for the mental health and moral development of a person, family, group, and social community.